A 2-year longitudinal evaluation of the iStent inject® system for open-angle glaucoma in East Asian eyes - Ru Jian Jonathan Teoh; Rupini Yogesvaran; Felicia Foo Yuen Cheng; Roslinah Muji (Oman Journal of Ophthalmology, 2025)
BACKGROUND: The aim of the study was to assess the midterm efficacy and safety of the iStent glaucoma device in patients with open-angle glaucoma (OAG). MATERIALS AND METHODS: We conducted a retrospective case series of all patients implanted with iStent inject® in OAG. Primary outcomes included intraocular pressure (IOP) and the reduction of antiglaucoma medications. Safety outcomes comprised adverse complications, additional surgeries, and postoperative best-corrected visual acuity (BCVA). RESULTS: Eight eyes from eight patients were included in this series. The mean age was 56.3 ± 17.5 years. Six eyes had primary OAG and two eyes had secondary OAG. The majority of eyes (75%) had mild-to-moderate glaucoma. Five eyes underwent combined surgery, whereas the remaining three eyes underwent a standalone procedure. The mean baseline IOP was 22.9 ± 8.2 mmHg, and the mean IOP at 2 years after the procedure was 13.6 ± 2.8 mmHg. There was a 44.5% (10.2 ± 2.5 mmHg; P = 0.002) IOP reduction over 2 years. There was also a reduction in medication burden from a baseline mean of 3.4 ± 0.7 to 2.0 ± 1.2 (P = 0.17). There was no documented intraoperative adverse complication, whereas one patient required trabeculectomy post iStent for IOP control. CONCLUSION: iStent inject implantation safely reduced IOP and medication burden up to 24 months postoperative.